Surgical Technique for Removal of Old Universal Slotted AO Femoral Nail: A Case Report - Naoko Onizuka; Brenton Douglass; Marc Swiontkowski (Case Reports in Orthopedics)
This paper presents a surgical technique for the removal of an old universal femoral nail preceding total hip arthroplasty (THA) in a 50-year-old male patient with left hip osteoarthritis. The patient had undergone femur nail insertion approximately 35 years ago. Due to the necessity of nail removal prior to THA, surgery to remove the nail was planned. There are challenges posed by the design of the old universal femoral nail system, particularly its side slot which made engagement of the conical bolt difficult. The successful removal of the nail was eventually achieved, enabling subsequent THA. Individuals who received this old implant years ago may now require its removal as part of osteoarthritis treatment. Given the lack of familiarity among surgeons with this outdated implant, this paper is aimed at providing essential guidance and insights regarding its removal procedure. This literature represents the inaugural documentation of the surgical technique for the removal of an aged femur nail.